2016
DOI: 10.1007/s12053-016-9476-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy saving in the street lighting control system—a new approach based on the EN-15232 standard

Abstract: The street lighting is one of major components in total energy consumption in cities. The paper is focused on a concept of street lamp control systems and function organization with remote monitoring, to reduce maintenance costs and energy consumption. A new approach to the definition of functional strategy organization for outdoor lighting systems is introduced in the paper. Proposed functional strategies are based on four efficiency classes of building automation and control systems (BACS) defined in the EN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…The authors concluded that the BACS with TBM functions should be taken into consideration in future regulations and in national law on the energy performance of buildings. Similar suggestions with introduction of appropriate tools supporting buildings design process and taking into account the EN 15232 requirements are provided by the author of this paper in previous publications [27,56]. Moreover, in [79] the author presents a case study focusing on experimental verification of the impact of the BACS with TBM functions organized according to the EN 15232 guidelines on the energy performance of a typical university classroom.…”
Section: Energy Efficiency Of Building-integrated Prosumer Microgridsmentioning
confidence: 81%
See 2 more Smart Citations
“…The authors concluded that the BACS with TBM functions should be taken into consideration in future regulations and in national law on the energy performance of buildings. Similar suggestions with introduction of appropriate tools supporting buildings design process and taking into account the EN 15232 requirements are provided by the author of this paper in previous publications [27,56]. Moreover, in [79] the author presents a case study focusing on experimental verification of the impact of the BACS with TBM functions organized according to the EN 15232 guidelines on the energy performance of a typical university classroom.…”
Section: Energy Efficiency Of Building-integrated Prosumer Microgridsmentioning
confidence: 81%
“…The first two have been discussed in numerous research and studies. However, the third factor is not so obvious, but in recent years it has been taken into consideration especially by building automation engineers [27,56,[72][73][74][75][76][77]. As a result, the mentioned EN 15232 standard has been introduced in 2007 and revised in 2012 [28].…”
Section: Energy Efficiency Of Building-integrated Prosumer Microgridsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual control, which is the earliest method employed in tunnel lighting, consists of turning lights on and off for different lighting circuits by the monitoring persons according to driving characteristics in an expressway tunnel during the day [19][20][21]. Sequential control divides the tunnel lighting operational modes into several categories according to the seasons and hours of the day [22]. Even though the two above methods are reliable and easy to implement in practice, the low degree of automation results in poor continuity and uniformity of luminance in tunnel interior [23].…”
Section: Tunnel Lighting Control Methods Literature Reviewmentioning
confidence: 99%
“…In the presence of automation and building management mechanisms in accordance with EN 15232:2007 [23], the efficiency of the use of trigeneration [24] for different zones of warehouses is obvious. This leads to the emergence of the issue of demand-side management for electricity.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%